Therapeutic Outcomes of Transplanting Autologous Granulocyte Colony-stimulating Factor-mobilised Peripheral Mononuclear Cells in Diabetic Patients with Critical Limb Ischaemia - Mohammadzadeh, L.; Samedanifard, S. H.; Keshavarzi, A.; Alimoghaddam, K.; Larijani, B.; Ghavamzadeh, A.; Ahmadi, A. S.; Shojaeifard, A.; Ostadali, M. R.; Sharifi, A. M.; Amini, M. R.; Mahmoudian, A.; Fakhraei, H.; Aalaa, M.; Mohajeri-Tehrani, M. R. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The efficacy and safety of transplanting autologous mesenchymal stem cells (MSCs), from granulocyte-colony-stimulating factor (G-CSF)-mobilised peripheral blood, was investigated in diabetic patients with critical limb ischaemia (CLI).After 3 months, the transplanted group of patients (n=7) showed a significant improvement in ischaemia manifestations, including pain and neurological signs, wound healing and the rate of lower-limb amputation, compared to the control group of patients (n=14). Pain was significantly reduced in the transplanted group compared to controls (P=0.014). The ankle-brachial index (ABI) and the pulse strength within ischaemic tissues of the transplanted group were significantly improved (P=0.035 and P=0.01, respectively).Importantly, 50% of the control group (7/14 patients) faced major amputation of a limb at the study’s conclusion, compared to none of 7 patients in the transplanted group (P=0.047).The safety of transplantation was confirmed by observing no adverse reactions among the transplanted group, including infection and immunological rejection.Hence, this study provides further evidence that transplantation of autologous peripheral blood MSCs, mobilised by G-CSF, induces angiogenesis and improves the wound healing process in diabetic patients with CLI.
Keywords: peripheral arterial disease; critical limb ischemia; stem cell transplantation